Exploring Students’ Attitudes Toward Integrating Artificial Intelligence (AI) in STEM Learning - Kan’an, Dr. Ashraf Fouad (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2025)
This study investigated students’ attitudes toward integrating Artificial Intelligence (AI) in STEM education. It focused on differences in attitudes based on gender, age, experience, and academic discipline. Using a descriptive survey design, the study gathered quantitative data from 360 students enrolled in STEM-related courses at Irbid National University, Jordan, during the second semester of the 2023–2024 academic year. The data were collected via an online questionnaire adapted from established literature. SPSS Version 23 was used to analyze the data; means, standard deviation, rank and multiple analyses of variance and comparisons using Scheffe’s method were calculated to answer the study questions. Results indicate that students generally hold positive attitudes towards the use of AI in STEM education with high grades. However, no significant differences were found in attitudes based on gender and age. In contrast, statistically significant differences emerged based on college affiliation, with Science and Information Technology students displaying more favorable attitudes than their Educational Sciences peers